Dampak Perkembangan Revolusi Industri 4.0 Terhadap Pendidikan Di Era Globalisasi Saat Ini - Rahma Syerlita; Irwan Siagian (Departement of Mathematics Education, 2024)
Globalization has a significant impact on various aspects of life throughout the world, including in the field of education. The current era is characterized by the rapid development of information and communication technology, influencing how education adapts and evolves. The Industrial Revolution 4.0 brings profound transformation in the economy, industry, and education with the adoption of advanced technologies such as artificial intelligence, Internet of Things (IoT), and cloud computing. Education must adapt quickly, introduce digital technology in learning, and integrate the 4C skills (Critical Thinking, Communication, Collaboration, Creativity) to prepare students to face future challenges. Apart from that, the industrial revolution 4.0 also has impacts including the development of learning methods, faster and more efficient learning services, new challenges and opportunities, changes in ways of learning and teaching, skills expected from teaching staff, changes in assessment evaluation, and challenges of equal access. This research uses a descriptive approach with quantitative analysis to understand the impact and use of the Industrial Revolution 4.0 in current global education. Discussions on the integration of digital technology in learning, digital skills development, and global collaboration highlight how education can improve the accessibility, personalization, and quality of learning in an increasingly globally connected era.